INEQUALITIES FOR ZEROS of JACOBI POLYNOMIALS VIA OBRECHKOFF'S THEOREM - Area, Ivan; Dimitrov, Dimitar Kolev [UNESP]; Godoy, Eduardo; Rafaeli, Fernando R. [UNESP] (Amer Mathematical Soc, 2012)
In this paper we obtain sharp limits for all the zeros of Jacobi polynomials. We employ Obrechkoff's theorem on generalized Descartes' rule of signs and certain elaborated connection formulae which involve Jacobi and Laguerre polynomials.
Keywords: Connection formula; Obrechkoff's theorem; Zeros; Jacobi polynomial; Laguerre polynomial